Epilepsy in tuberous sclerosis patients in Sweden – Healthcare utilization, treatment, morbidity, and mortality using national register data. (December 2017) - Welin, Karl-Olof; Carlqvist, Peter; Svensson, Anders; Althin, Rikard; Eklund, Erik; Rask, Olof
Highlights: Register study of all TSC patients with epilepsy in Sweden during 2004–2013. The prevalence of epilepsy is lower than in previous studies of TSC patients. 97.9% of patients have been prescribed antiepileptic drugs at some point. Epilepsy make up a significant part of healthcare use in TSC patients with epilepsy. Abstract: Purpose: This study is designed to estimate the prevalence of epilepsy associated with TSC in Sweden and to describe treatment, morbidity, and mortality of TSC patients with epilepsy. Methods: Register data for 2004–2014 was obtained from the National Board of Health and Welfare in Sweden. Patients with TSC were identified using ICD-10 codes. Epilepsy was identified using ICD-10 codes, interventions aimed to treat epilepsy, or prescriptions for antiepileptic drugs. Results: The prevalence of TSC was 5.38 per 100 000 individuals. We identified 551 unique patients with TSC, of which 386 (70.1%) had epilepsy. The mean study period was 8.82 years. Antiepileptic drugs were dispensed to 97.9% of patients with epilepsy. The most prescribed antiepileptic drug was sodium valproate. Ketogenic diet was used in 6 (1.6%) patients, vagus nerve stimulation in 23 (6.0%) patients, and epilepsy surgery was performed in 25 (6.5%) patients. The mean number of outpatient visits per year was 4.70 (SD 4.17) and the mean number of inpatient days per year was 3.25 (SD 5.61). The mean number of outpatient visits per year with an ICD-10 code for epilepsy was 1.65 (SD 1.95) and the corresponding number of inpatient days was 2.06 (SD 4.50). A total of 30 patients with TSC and epilepsy died during the study period. Conclusions: The prevalence of epilepsy in this study was in the lower range of previously reported numbers, suggesting that epilepsy may be overestimated in non-population based studies. A substantial part of the healthcare utilization was directly related to epilepsy.